Osteocartilaginous choristoma of the tongue: a case report and review of the literature - Câmara, Priscilla Rodrigues; Santos, Jefferson Ferreira dos; Monteiro, Maria Carolina de Lima Jacy; Menezes, Rafaela Elvira Rozza de; Gouvêa, Adriele Ferreira; Fontes, Karla Bianca Fernandes da Costa; Azevedo, Rebeca Souza; Tucci, Renata (Journal of Oral Diagnosis, 2017)
The purpose of the present article was to report a clinical case of a 53-year-old male patient with a tongue osteocartilaginous choristoma. Additionally, we made a brief review of the literature to identify all cases reported in English-language literature of oral osteocartilaginous choristoma and, to the best of our knowledge, there are only nine reported cases. Choristoma is a lesion characterized by the development of a histologically normal tissue in an abnormal site. Occurrence of osseous or cartilaginous choristomas in oral soft tissues are rather uncommon. Cases presenting both bone and cartilage simultaneously, named osteocartilaginous choristomas, are even rarer. After the literature search, we also compare the pathogenesis, clinical and histopathological features of our osteocartilaginous choristoma with the literature about osseous or cartilaginous choristomas. The present case report contributes with an additional case of osteocartilaginous choristoma of the tongue, which is suggestive of metaplasia, and it had an unusual histopathological aspect with cartilage structure as principal component.